Seaweed-Derived Proteins and Peptides: Promising Marine Bioactives - Javier Echave; Paz Otero; Paula Garcia-Oliveira; Paulo E. S. Munekata; Mirian Pateiro; Jose M. Lorenzo; Jesus Simal-Gandara; Miguel A. Prieto (MDPI AG, 2022)
Seaweeds are a typical food of East-Asian cuisine, to which are alleged several beneficial health effects have been attributed. Their availability and their nutritional and chemical composition have favored the increase in its consumption worldwide, as well as a focus of research due to their bioactive properties. In this regard, seaweed proteins are nutritionally valuable and comprise several specific enzymes, glycoproteins, cell wall-attached proteins, red algae phycobiliproteins, lectins, peptides, or mycosporine-like amino acids. This great extent of molecules has been reported to exert significant antioxidant, antimicrobial, anti-inflammatory, antihypertensive, antidiabetic, or antitumoral properties. Hence, knowledge on algae proteins and derived compounds have gained special interest for the potential nutraceutical, cosmetic or pharmaceutical industries based on these bioactivities. Although several molecular mechanisms of action on how these proteins and peptides exert biological activities have been described, many gaps in knowledge still need to be filled. Updating the current knowledge related to seaweed proteins and peptides is of interest to further asses their potential health benefits. This review addresses the characteristics of seaweed protein and protein-derived molecules, their natural occurrence, their studied bioactive properties, and their described potential mechanisms of action.